Simulating Southern Ocean Aerosol and Ice Nucleating Particles in the Community Earth System Model Version 2. Issue 8 (14th April 2023) - McCluskey, Christina S.; Gettelman, Andrew; Bardeen, Charles G.; DeMott, Paul J.; Moore, Kathryn A.; Kreidenweis, Sonia M.; Hill, Thomas C. J.; Barry, Kevin R.; Twohy, Cynthia H.; Toohey, Darin W.; Rainwater, Bryan; Jensen, Jorgen B.; et al.
Abstract: Southern Ocean (SO) low‐level mixed phase clouds have been a long‐standing challenge for Earth system models to accurately represent. While improvements to the Community Earth System Model version 2 (CESM2) resulted in increased supercooled liquid in SO clouds and improved model radiative biases, simulated SO clouds in CESM2 now contain too little ice. Previous observational studies have indicated that marine particles are major contributor to SO low‐level cloud heterogeneous ice nucleation, a process that initiates a number of cloud processes that govern cloud radiative properties. In this study, we utilize detailed aerosol and ice nucleating particle (INP) measurements from two recent measurement campaigns to assess simulated aerosol abundance, number size distributions, and composition and INP parameterizations for use in CESM2. Our results indicate that CESM2 has a positive bias in simulated surface‐level total aerosol surface area at latitudes north of 58°S. Measured INP populations were dominated by marine INPs and we present evidence of refractory INPs present over the SO assumed here to be mineral dust INPs. Results highlight a critical need to assess simulated mineral dust number and size distributions in CESM2 in order to adequately represent SO INP populations and their response to long‐term changes in atmospheric transport patterns and land use change. We also discuss important cautions and limitations in applying a commonly used mineral dust INP parameterization to remote regions like the pristine SO. Plain Language Summary: Clouds over the Southern Ocean play an important role in our climate by reflecting significant amounts of solar radiation that would otherwise be absorbed by the ocean. Earth system models used to simulate climate struggle to accurately represent Southern Ocean clouds, largely because there have been limited observations to evaluate and improve models. One specific process that may be important for modeling Southern Ocean clouds is ice nucleation, where ice nucleation active particles serve as "seeds" for ice formation in clouds. In this study, we use measurements from two recent field campaigns to test a state‐of‐the‐art Earth system model's representation of atmospheric particles. We also test three different methods for representing the concentrations of available ice nucleating particles. The results from this work highlight a need for increased knowledge of the quantities, sizes and altitudes of mineral dust particles transported from distant land sources to the Southern Ocean and also emphasizes that Earth system models need to include ice nucleation from marine particles in order to accurately represent aerosol‐cloud‐climate interactions in these remote regions. Key Points: Marine and mineral dust aerosol contributed to ice nucleating particle populations measured from ship and aircraft over the Southern Ocean The model predicts observed latitudinal variability in aerosol surface area concentrations at high southern latitudes Model‐predicted mineral dust ice nucleating particle number concentrations vary by 4 orders of magnitude over the Southern Ocean